(untitled) (Publicaciones en Ciencias y Tecnología, 2018)
The objective of this work is to present the elaboration of a Minimum Plan of Prevention of Working Risks for the microcompany (Microenterprise es más usado) "Lavadora and Lubricadora Cantos Jr." of the canton Puerto Lopez, in Ecuador. The health and safety at work policy has been defined. The risk factors at the workplace have been identified, measured and evaluated in order to propose some control measures that will ensure the prevention of occupational injuries and illnesses. The development of this work was based on the William Fine risk assessment method and Istas 21 method, and the application of the Risk Working Matrix. For the elaboration of the Minimum Plan for the Prevention of Occupational Risks, the format issued by the Ministry of Labor Relations is considered, adjusted to the ruling policy in this matter, and to the technical management of the Regulations for the Workplace Risk Audit System. As a result, the definition of the policy, chapters, and articles adapted to the microenterprise under study are highlighted, to ensure the safety and health of its workers.